Effect of Feeder Modification and Feed Form on Feed Loss and Conversion Efficiency in Small-Scale Broiler Farms - Al-Atiyat, Raed; Abdel-Ghani, Adel; khmaiseh, Sami (The Iraqi Journal of Veterinary Medicine, 2025)
Feed losses in broiler farms are negatively affecting the health and growth of broiler and thus reducing profitability. This study aimed to estimate feed loss in small-scale broiler farms using two modified conventional feeders, Trough and Tube feeders, and two different feed forms, Mash and Pellet. The experiment was carried out using non-modified feeders and modified by attaching a 4×4 cm protective net to Trough feeder and reducing length from 6 cm to 4 cm to Tube feeder. Results showed a very slight effect of feeder type on feed loss for the benefit of the Trough feeder. The feed losses were significantly noted (from 3.91% to 1.84% before and after modification, respectively) when feeding Mashed feed with Trough feeder.  Similarly, it was significantly reduced from 8.17% to 2.10% before and after modification, respectively, when fed Pelleted feed with Trough feeder. However, the feed loss decreased as the older the broiler chicken gets (losses reduced from 9.93% in the 4th week to 2.39% in the 7th week). Feed loss was significantly increased when feeding pellet feed (loss=10.76%) as compared to mashed feed (feed loss=2.60%). The feed conversion ratios (FCR) were 1.93 and 1.88 when Trough and Tube feeder types were used, respectively. The feed losses were reduced from 7.32% to 0.75% and 6.04% to 1.97% for modified Tube and Trough feeders, respectively. In conclusion, feed loss was decreased as the broiler age increased, and the loss rate was higher using Pellet feed compared to Mash feed. Summing up, modified feeder by itself had no significant effect on feed loss, even though feed loss was substantially reduced, and FCR was improved‎‎‎.